Time‐Varying Emulator for Short and Long‐Term Analysis of Coastal Flood Hazard Potential. Issue 12 (17th December 2019) - Anderson, D.; Rueda, A.; Cagigal, L.; Antolinez, J. A. A.; Mendez, F. J.; Ruggiero, P.
Abstract: Rising seas coupled with ever increasing coastal populations present the potential for significant social and economic loss in the 21st century. Relatively short records of the full multidimensional space contributing to total water level coastal flooding events (astronomic tides, sea level anomalies, storm surges, wave run‐up, etc.) result in historical observations of only a small fraction of the possible range of conditions that could produce severe flooding. The Time‐varying Emulator for Short‐ and Long‐Term analysis of coastal flood hazard potential is presented here as a methodology capable of producing new iterations of the sea‐state parameters associated with the present‐day Pacific Ocean climate to simulate many synthetic extreme compound events. The emulator utilizes weather typing of fundamental climate drivers (sea surface temperatures, sea level pressures, etc.) to reduce complexity and produces new daily synoptic weather chronologies with an auto‐regressive logistic model accounting for conditional dependencies on the El Niño Southern Oscillation, the Madden‐Julian Oscillation, seasonality, and the prior two days of weather progression. Joint probabilities of sea‐state parameters unique to simulated weather patterns are used to create new time series of the hypothetical components contributing to synthetic total water levels (swells from multiple directions coupled with water levels due to wind setup, temperature anomalies, and tides). The Time‐varying Emulator for Short‐ and Long‐Term analysis of coastal flood hazard potential reveals the importance of considering the multivariate nature of extreme coastal flooding, while progressing the ability to incorporate large‐scale climate variability into site specific studies assessing hazards within the context of predicted climate change in the 21st century. Plain Language Summary: Predicting extreme coastal flooding is a present‐day societal need and will only become more relevant as mean water levels increase due to sea level rise. However, the number of processes contributing to such events is too high for relatively short observational records to have measured all of the constructive combinations of waves, surge, wind, and sea level anomalies. We present a framework designed to create hypothetical combinations of relevant flood hazard potential processes by simulating the climate and weather patterns that drive coastal flooding. Including large‐scale oceanic and atmospheric patterns as the drivers of coastal hazards reveals the climate a coastal community is most vulnerable to, which will be increasingly more important to understand as the climate changes during the 21st century. Key Points: Stochastic climate emulator explicitly links climate patterns to local coastal flooding components (waves, surges, sea level anomalies, etc.) Thousands of years of synthetic total water levels are directly simulated via individual components producing long return period event magnitudes Conservation of temporal structure and persistence of interannual, seasonal, and intra‐seasonal time scales